Exploring The Impact Of Learning Discipline On Indonesian Language Learning In High-Level Primary Schools - Syahfira, Abel Dea (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Discipline can have a significant impact on student learning outcomes. It is believed that instilling a disciplined attitude towards learning can assist children in achieving success at school. In high-grade elementary schools, guidance activities that promote discipline in learning have been found to have a significant impact on Indonesian language learning outcomes. Tutoring is one measure that can be used to assess learning success for elementary school students. This study explores the effects of discipline guidance on the learning outcomes of Indonesian students. To ensure positive behaviour among elementary school children, it is important to instil the value of discipline in them. Negative consequences, such as incomplete assignments or disobedience of school rules, can result from deviant behaviour, which is not worth emulating. Therefore, it is crucial to teach elementary school children the importance of discipline for their own benefit. Hence, it is crucial to encourage the development of discipline from a young age, as it can become a habitual practice that will have a long-term effect on their behaviour as they mature.